When less is more: Visitation by generalist pollinators can have neutral or negative effects on plant reproduction - Burns, Cole; Villalobos, Soraya; Vamosi, Jana C. (Frontiers in Ecology and Evolution, 2022)
Selection for specialized coevolutionary relationships can arise if generalized opportunistic pollinators, while still delivering some pollen, operate as less effective pollen delivery agents. Nevertheless, generalization could buffer high-latitude communities from loss of specialist pollinator species by providing some pollination service. Currently, there is limited understanding of the ecosystem services provided by generalized pollinators and whether they increase the fitness of the plants they visit. Network data and thorough observations of floral visitors, paired with estimates of seed set, offer some insight into the role of generalists, which in turn can inform us about how plants are likely to respond to ecosystem disturbances, such as losses of some pollinators, or changes in land cover. Here, we report on a plant-pollinator visitation networks in Canada with high levels of generalization and examine the effects of generalization on seed set under different disturbance histories. We also then take a case study of one crop wild relative, Rubus arcticus or Arctic raspberry, and report on a near-complete characterization of pollinator interactions in different environmental conditions. Our findings indicate that generalized pollinators, though frequent and robust to variable temperatures and moisture conditions, do not appear to play a strong role in increasing the reproductive output of many plant species, and may provide only a weak buffer against the stronger effects of disturbance.